FACTORS INFLUENCING JOB SATISFACTION AMONG NURSES WORKING AT BMC HOSPITAL, QUETTA (The Research of Medical Science Review, 2025)
Background: Nursing is a highly sensitive and demanding profession that requires nurses to be in both good physical and mental health. Best nursing care can be directly influenced by satisfaction level of nurses working within their roles. When nurses are highly satisfied, the quality of patient care tends to be excellent. Conversely, if nurses are dissatisfied with the facilities and conditions in which they work, the quality of care they provide can suffer. Methods: This study employed a descriptive, cross-sectional research design and included a total of 100 nurses with a minimum of 6 months of experience at BMC Hospital. The participant’s selection was done using simple random sampling technique. Data collection was carried out by using a questionnaire that has been already tested using self-administered method that included a job satisfaction scale with 24 domains. The collected data was entered into SPSS version 16.0 for analysis, utilizing both statistical measure like inferential and descriptive methods including chi-square test too. Results: Among the 100 participants, the majority of nurses (63.2%) reported being moderately satisfied with their jobs, while 28.8% expressed dissatisfaction, and 12.3% reported being somewhat satisfied. A smaller percentage (3.8%) were fully satisfied with their jobs according to the Likert scale. The study revealed significant associations between job satisfaction levels and certain demographic factors, including age (P-Value: 0.029) and educational level (P-Value: 0.058), both of which were found to be highly significant (P < 0.05). Among the 24 different factors assessed, specific factors impacting job satisfaction included working hours, the work environment, interpersonal relationships within the institution, supervision systems, opportunities for advancement, training, conferences, workshops, and leave policies. Conclusion: In summary, this study highlights the numerous factors that can influence the job satisfaction levels of nurses, subsequently impacting the quality of patient care and healthcare organizations. To enhance job satisfaction and improve patient care, priority should be given to addressing working hours, the work environment, interpersonal relationships, and supervision systems within healthcare institutions. Additionally, emphasis should be placed on providing opportunities for career growth, promotion, and training to ensure a brighter future for nursing and the delivery of quality patient care.